Molecular Basis of S100A1 Activation and Target Regulation Within Physiological Cytosolic Ca2+ Levels - Sun, Bin; Kekenes-Huskey, Peter M. (Frontiers in Molecular Biosciences, 2020)
The S100A1 protein regulates cardiomyocyte function through its binding of calcium (Ca2+) and target proteins, including titin, SERCA and RyR. S100A1 presents two Ca2+ binding domains, a high-affinity canonical EF-hand (cEF) hand and a low-affinity pseudo EF-hand (pEF) hand, that control S100A1 activation. For wild-type S100A1, both EF hands must be bound by Ca2+ to form the open state necessary for target peptide binding, which requires unphysiological high sub-millimolar Ca2+ levels. However, there is evidence that post-translational modifications at Cys85 may facilitate the formation of the open state at sub-saturating Ca2+ concentrations. Hence, post-translational modifications of S100A1 could potentially increase the Ca2+ -sensitivity of binding protein targets, and thereby modulate corresponding signaling pathways. In this study, we examine the mechanism of S100A1 open-closed gating via molecular dynamics simulations to determine the extent to which Cys85 functionalization, namely via redox reactions, controls the relative population of open states at sub-saturating Ca2+ and capacity to bind peptides. We further characterize the protein’s ability to bind a representative peptide target, TRKT12 and relate this propensity to published competition assay data. Our simulation results indicate that functionalization of Cys85 may stabilize the S100A1 open state at physiological, micromolar Ca2+ levels. Our conclusions support growing evidence that S100A1 serves as a signaling hub linking Ca2+ and redox signaling pathways.